Expanding the viewshed: Insights and implications for examining visitor use management across scales and modalities in an Iconic National Forest. (December 2022) - Ferguson, Michael D.; Perry, Elizabeth E.; Lynch, Myles; Ferguson, Lauren A.; Kiewra, Lydia A.; Leberman, Marianne; Koopman, Alison; Barcelona, Robert; Reigner, Nathan P.; Manning, Robert E.
Abstract: The recent increase in demand for outdoor recreation opportunities within parks and protected areas (PPAs) has impacted visitor experiences, natural resources, and resource management. Outdoor recreation research and management practices often employ single survey modalities to assess a recreation issue at a specific location and time. This research approach has historically met the challenge of helping to alleviate strains associated with social and ecological impacts in PPAs. Recent research in the areas of social-ecological systems (SES) and hierarchy theory, however, suggests an adaptive systems approach, spanning various scales (e.g., spatial, temporal, topical) and modalities (e.g., on-site, off-site, big data), may be the most comprehensive approach to recreation research and management. The current study examined visitor perceptions of crowding, use-levels, encounter rates, management preferences, and overall experience quality within spatial and temporal scales and on-site and off-site survey modalities at the White Mountain National Forest (WMNF), USA. Specifically, this study compared data within two distinct WMNF studies: 1) a 2016 on-site study (n = 855) and 2) a 2020 off-site study (n = 642). Respondents within these separate, yet complementary studies, were segmented by both frequency of visitation and distance traveled to the WMNF. Descriptive and inferential statistics determined that while there are indeed commonalities between the two samples, respondent profiles and overall perceptions of crowding, encounter rates, and management preferences have different trend pattens between samples, with significant differences within samples. Study findings suggest the employment of multiple scales and modalities may provide greater context, validity, and nuance to complex SES outdoor recreation issues which, in turn may provide a more comprehensive understanding of visitor needs. This research provides empirical evidence to support both the SES and hierarchy theory frameworks and underscores the importance and utility of employing an adaptive systems approach for sustainable PPA management. Management implications: Results from this study found general commonalities between the on-site and off-site study samples. However, respondent profiles and overall perceptions of crowding, encounter rates, and management preferences have different trend pattens between samples, with significant differences within samples. Respondents in the on-site study sample were predominantly non-locals who visited the WMNF infrequently, perceived moderate levels of overall crowding, preferred higher-use site stratums, and had a very high threshold for maximum visitor encounters per day. Respondents in the off-site study sample, however, trended toward the opposite. Results indicate different modalities of data collection provide substantially different results within the same geographic region and, together, may provide a more precise understanding of the area and related recreation impacts. Study findings suggest recreation researchers and resource managers should consider applying multiple scales and modalities in order to comprehensively assess and understand complex human-nature relationships.